The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/0366-6999.221274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Differential Diagnosis of Desmoplastic Fibroblastoma by Clinical, Radiological, and Histopathological Analyses

Abstract: Background:Desmoplastic fibroblastoma (collagenous fibroma) is an uncommon benign soft-tissue tumor, rarely involving bone. It shares some overlapping features with other infiltrate tumors, such as desmoid-type fibromatosis, neurofibroma, and low-grade fibromyxoid sarcoma. The misdiagnosis may cause unnecessary surgical overtreatment, especially for those involving bone. In order to deepen the understanding of the diagnosis and differential diagnosis of desmoplastic fibroblastoma, we planned to analyze the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Desmoplastic fibroblastomas (DFs) are uncommon benign fibrous soft tissue tumors typically occurring between the ages of 40 and 69 and are rarely observed in the tongue, palate, and neck. 4 DFs are composed of fibroblasts/myofibroblasts with variable collagen formation and are also known as collagenous fibromas 5,6 due to their tendency to show abundant collagen formation which has historically been used as a diagnostic clue. Available literature describes a few rare cases of DFs of the hard palate and oral cavity 6,7 and one case in the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Desmoplastic fibroblastomas (DFs) are uncommon benign fibrous soft tissue tumors typically occurring between the ages of 40 and 69 and are rarely observed in the tongue, palate, and neck. 4 DFs are composed of fibroblasts/myofibroblasts with variable collagen formation and are also known as collagenous fibromas 5,6 due to their tendency to show abundant collagen formation which has historically been used as a diagnostic clue. Available literature describes a few rare cases of DFs of the hard palate and oral cavity 6,7 and one case in the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Desmoplastic broma of bone (BFB) is a rare benign tumor with local aggressiveness and in ltration and has well-differentiated myo broblasts microscopically with rich deposition of dense collagens [1][2][3] . The prevalence of DFB is 0.06%-0.11% in all primary bone tumors and 0.3% in benign bone tumors [1][2][3][4][5][6] . This tumor occurs mostly in males between the ages of 16 and 83 years (median 50), and the primary locations of this tumor are the long bones (56%) followed by mandible (26%) and pelvis (14%).…”
Section: Introductionmentioning
confidence: 99%
“…This tumor occurs mostly in males between the ages of 16 and 83 years (median 50), and the primary locations of this tumor are the long bones (56%) followed by mandible (26%) and pelvis (14%). The imaging characteristics of this tumor are well-de ned osteolytic lesions with destruction of cortical bone, marginal osteosclerosis, and pseudotrabeculation, which are not speci c and cannot be differentiated from those of other bone tumors like brous dysplasia, eosinophilic granuloma, hemangioma, and central low-grade osteosarcoma [1][2][3][4][5][6] . Because of the rarity and nonspeci c imaging presentations of this tumor, it is di cult to diagnose and differentiate it from other tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Typically, DFB is more common in the distal femoral metaphysis when it occurs in the femur. [3] Moreover, although DFB can occur at any age, the morbidity in young people is much higher than that in the elders. Evidence has revealed that DFB is lytic, occasionally with poorly defined borders on X-ray.…”
Section: Introductionmentioning
confidence: 99%